THE COMPARATION OF MAQᾹṢῙD IMPLIMENTATION’S IBN ‘AṢŪR AND MUNᾹWIR SJADZALI’S IN QS. 4: 11 - Shofa, Ida Kurnia (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This paper will discuss the discourse of inheritance in QS. 4: 11 according to modern figure, Ibn ‘Aṣūr and Munawar Sjadzali. So, the purpose of this reseach is to express base of maqāṣīd application that used by them. This research is library research with diskriptive-analysis and comparation method. The result of this research is that two figures found a significant values in that surah with different maqashid concept. Ibnu ‘Aṣūr understood the surah (QS. 4: 11) is as an awarding attention for muslem women in the discourse of inheritance that they get a half of a man proportion. Even before the revelation of that surah, the women’s right were not given. While, Munawir Sjadzali understood that surah by searching an ideal value and contextualize whit the situation and condition in his country with formulation 1:1 for man and women which considered the roles and positions woman are relatively same with a man along the demands of the times.